2007
DOI: 10.1080/07060660709507447
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effects of a climate-change scenario on the geographical range and activity of forest-pathogenic fungi

Abstract: The aim of the study was to explore possible effects of climate change on the geographic range or local impact of several forest pathogenic fungi. To this aim, (1) the parameters of species' responses to climatic variables were determined, in two types of models: specific statistical models and the generic model CLIMEX; (2) these models were used to make simulations under a future climatic scenario, based on a general circulation model of climate, which was regionalized over France. A range of pathogens common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
127
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(135 citation statements)
references
References 78 publications
(82 reference statements)
4
127
0
Order By: Relevance
“…The trade has also increased the spread of associated organisms, some of which are plant pathogens (Hansen 2008, Desprez-Loustau et al 2010. Simultaneously, climate change predictions are going to affect the distribution and virulence of pathogens, many of which have not been considered important because of an unfavorable climate (Desprez-Loustau et al 2007). It is interesting that although the ornamental plant trade has obviously been the most frequently utilized pathway for pathogens to reach Finland, organisms arriving by more natural means have so far caused the most extensive damage.…”
Section: Discussionmentioning
confidence: 99%
“…The trade has also increased the spread of associated organisms, some of which are plant pathogens (Hansen 2008, Desprez-Loustau et al 2010. Simultaneously, climate change predictions are going to affect the distribution and virulence of pathogens, many of which have not been considered important because of an unfavorable climate (Desprez-Loustau et al 2007). It is interesting that although the ornamental plant trade has obviously been the most frequently utilized pathway for pathogens to reach Finland, organisms arriving by more natural means have so far caused the most extensive damage.…”
Section: Discussionmentioning
confidence: 99%
“…Such risks are likely to increase in the near future due to rising temperatures and an increased recurrence of major climatic events (Kovats et al 2014). Moreover, it has been demonstrated that a rise in temperature leads to an increase of some biotic hazards (Rouault et al 2006), whereas the increase in frequency and intensity of some natural hazards favors the development of phytosanitary problems (Desprez-Loustau et al 2007;Berggren et al 2009). In addition to these climate factors, human activities are also likely to increase species displacement rates by intentionally or unintentionally dispersing individuals or propagules.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al 2004;Bergot et al 2004;Garrett et al 2006;Desprez-Loustau et al 2007;Chakraborty et al 2008;Evans et al 2008;La Porta et al 2008;Pautasso et al 2010). Several fungal diseases in trees can become more devastating because of the following factors: (i) abiotic stresses, such as drought and flooding, are known to predispose trees to several pathogens; (ii) temperature and moisture affect the pathogen sporulation and dispersal, and changes in climatic conditions are likely to favour certain pathogens; (iii) the migration of pathogens triggered by climatic change may increase disease incidence or geographical range when the pathogens encounter new hosts and/or new potential vectors; (iv) new threats may appear either because of a change in the tree species composition or because of invasive species (La Porta et al 2008).…”
mentioning
confidence: 99%
“…In this century, the winter temperature can reach from 3.0°C to 4.0°C in Central and Eastern Europe; the average winter temperature can exceed 0°C, and the change in climate can specifically concern the lowest winter minimum temperatures (IPCC 2007). Recent models predict an increase in the distribution and local impact of a range of forest pathogens, including P. cinnamomi (Desprez-Loustau et al 2007). Winter survival is a dominant cue for the development of ink disease caused by this pathogen in oak in Europe (Brasier, Scott 1994;Marçais et al 1996;Bergot et al 2004).…”
mentioning
confidence: 99%